Life Conditions of Population of North Ossetia during Great Patriotic War - L. C. Khabliyeva; Z. V. Sosranova; Z. Y. Dzottsoyeva (Научный диалог, 2018)
The article is devoted to the description of living conditions of the population of North Ossetia in wartime. The authors use Republic and Russian archival materials to present system of food supply and catering, housing and medical care of Soviet citizens during the Great Patriotic war. It is emphasized that in difficult wartime conditions the state was forced to introduce a normalized supply of food and industrial goods as an emergency and necessary measure. The description of the differentiated principle of distribution of food among various categories of the population is given. It is noted that the measures taken by the party and state bodies of the North Ossetian Autonomous Soviet Socialist Republic to improve the social security of the population of the Republic, were aimed at ensuring the necessary minimum to maintain the viability of citizens. The authors emphasize that in general the normalized supply played an important role in providing the Soviet population with a minimum of food and consumer goods, but a large number of people experienced hunger during the war, which became one of the main causes of high mortality. The article attempts to explore various aspects of life of the population of the North Caucasus during the Great Patriotic war: housing and household problems, food supply, issues of preserving the health of citizens and health care.